Five continents - Vavilov, N.I. (1996)
Distribution limited to institution libraries. Finally published in English, this book contains descriptions by Academician N.I. Vavilov of the expeditions he made between 1916 and 1940 to five continents, in search of new agricultural plants and confirmation of his theories on plant genetic diversity. Vavilov is ironic, mischievous, perceptive, hilarious and above all scholarly. This book is a readable testament to his tenacity and belief in his work, in the face of the greatest adversity.